Improving Fitness Professional Education in Working With Older Adults — A Case Study From a Therapeutic Relationship Perspective - Ting, Chien Ju; Bercades, Luigi (Emerald, 2026)
Purpose As populations around the world, including Aotearoa New Zealand (NZ), continue to age, supporting the well-being of older adults has become increasingly important. Regular physical activity (PA) is a key contributor to healthy ageing and enhancing well-being. Fitness instructors play a crucial role in engaging older adults in ongoing PA; however, many trainers lack adequate training and support to work effectively with this population to sustain their long-term engagement. This study aims to explore the role of the therapeutic relationship (TR) in facilitating long-term and sustained engagement in PA among older adults. Specifically, it examines how fitness professionals (FPs) construct trust, negotiate power and foster adherence in ways that go beyond physical training alone. Design/methodology/approach In this case study, we focus on “expert voice” and interviewed two veteran trainers from the never2old exercise programme. We explore the aspects that contribute to the establishment of a TR, which is characterised by collaboration and trust. A Foucauldian discourse analysis approach is used to explain how power and trust can be co-constructed and shared. Findings The findings show how FPs construct trust, negotiate power and engage with older adults. The paper identifies concrete facilitators (self-disclosure, joint decision-making, communication strategies, innovation and autonomy), and makes practical recommendations to the current curricula for trainer education beyond creating a workout plan. Research limitations/implications This study highlights the need to reframe frailty discourse within FP education, moving beyond age-based deficit models towards strengths-based, self-determination approaches. It also shows that as NZ becomes more diverse in population, training needs to foster cultural awareness. While the research only contains expert interviews from two participants, their experience provided rich data to explore the case study. Further studies could draw on the older clients’ perspectives and co-design what is needed for the future curriculum. Practical implications Training should integrate motivational interviewing, intercultural competence and age-appropriate communication strategies to better support Aotearoa New Zealand’s super-diverse and ageing population. Institutional cultures that privilege narrow notions of “Kiwiness” require critical reflection to avoid exclusion. Promoting workplace autonomy and innovation may enhance practitioner engagement and client trust. The principle of the TR should be part of the curriculum. Social implications Socially, this study suggests that FP education can either reinforce or disrupt ageism and cultural exclusion. Reframing frailty as resilience challenges deficit-based views of older adults and supports dignity and participation. Strengthening intercultural competence is critical in Aotearoa New Zealand’s super-diverse context to ensure equitable access. Promoting autonomy and shared decision-making further enhances older adults’ agency, voice and social inclusion in later life. Originality/value This study presents a unique methodological approach, combining the theoretical lens of the TR with a Foucauldian approach, to offer evidence-informed implications for fitness trainers’ education.
Keywords: 3901 Curriculum and Pedagogy; 39 Education; 4206 Public Health; 42 Health Sciences; Physical Activity; Aging; Prevention; Behavioral and Social Science; Generic health relevance; Physical activity; Therapeutic relationship; Foucauldian discourse analysis; Fitness professional education; Never2old; Older adults